Tribology Effect On Turning Machine Process Using Jatropha Oil With AC Nanoparticle - Zolkefli, Ariff Azizi; Talib, Norfazillah (Research Progress in Mechanical and Manufacturing Engineering, 2022)
Synthetic-based lubricant is widely used in industry for metalworking fluid in machining. However, it can be dangerous to operator’s health and environment due to chemical components. Thereupon, a development of biodegradable oil with low toxicity has been taken as initiatives to be a substitute of existing lubricant. The purpose of this study was to formulate new environmentally friendly lubricant with modified jatropha oil (MJO) as based oil and activated carbon (AC) as nanoparticle at various concentrations (0.01wt%, 0.025wt% and 0.05wt%) and to analyze tribological performance in terms of cutting temperature tool wear and tool life using turning process. The tribological performance of MJO + AC was compared with benchmark oil, synthetic ester (SE) using minimum quantity lubricant technique (MQL). Tribological performances such as cutting temperature was recorded in the first 100 mm axial cutting length. From the result, MJO + 0.025wt% AC shows outstanding performance in cutting temperature compared to all samples. The addition of 0.025wt% of AC which had porous structure increases the adsorption thus provides protection layer and sufficient concentration of AC promotes rolling action. Hence, the experiment was continued using MJO + 0.025wt% AC and SE to compare tool wear in terms of average flank wear (VBB), maximum flank wear (VBBmax), notch wear (VBN) and tool life. MJO + 0.025wt% AC has longer tool life (7000mm cutting length at 49 minutes machining time) compared to SE (6000mm cutting length at 42 minutes machining time). In conclusion, MJO + 0.025wt% AC exhibit outstanding tribological performance and suitable to replace synthetic oil as MWF.